Adsorption behavior of phenolpthalein on electrospun PMMA/clay nanostructured fibers - Rodriguez, Ner Cruz. ("April 2009")
Locally modified clays namwly organoclay (nonclay), beneficiated (Al-bene) and Naactivated (Al-Na) clays were blended with polymethyl methacrylate (PMMA) and electrospun into fibers with diameter ranging from 6 to 19 um. Using the SEM, FTR and FT-Raman, fibers were investigated in terms of morphological structure, good functional property and mechanical property. SEM photomicrograph revealed the presence of pores on fibers blended with clay. Nanopores with diameter 80 nanometers were observed on the surface of the fibers. FTR and FT-Raman confirmed that PMMA/organoclay blend is best in terms of surface structure and physical property. A solution containing phenolphthalein (PHP) was used to study the adsorption behavior of the fibers to small organic molecules. Using UV -VIS, the adsorptions of PHP on different fiber blends were determined. PHP was adsorbed up to 65.3%, 62.4%, 61.4% and 60.7% unto orbanoclay blend, Al-beneficiated blend, Al-Na derived blend and pure PMMA, respectively, at a liquor-tosorbent ratio of 3333:1. Adsorption experiment confirmed that all 4 fibers fit to the Temkin model. However PMMA /Al-Bene fits more to the freundlich model. Scatchard plot was used to describe the binding of PHP onto the fiber blends. Resultshowed that PMMA/Al-Bene has homogenous binding sites for PHP while the other 3 fibers are heterogeneous. This study showed that addition of clay, with certain modification, may increase the capability of fibers to capture PHP and possibly other organic molecules in water.
Thesis (MS in Chemical Engineering)--University of the Philippines Diliman.
Keywords: Phenolphthalein